PENGOLAHAN BERAS KENCUR DAN JAHE SEBAGAI BAHAN DASAR MOCKTAIL - Amar Bhisma Winata; Dendi Gusnadi (Media Bina Ilmiah, 2024)
This study looks at how the hotel industry makes mocktails from kencur rice and ginger. In traditional practice, ginger and galangal are chosen for their health benefits. Experimental methods and organoleptic tests were used in this study to create mocktail recipes and assess consumer acceptability. In the processing process, extraction, filtering and distillation are carried out to produce a concentrated extract that is rich in active substances. Ginger beer is made by fermenting ginger, and kencur rice is processed into juice which is used in mocktails. In this study, forty panelists assessed the taste, aroma, texture and appearance of the mocktails made. The organoleptic test results show that the mocktail made from kencur rice and ginger is very popular with customers. This mocktail has received good reviews in terms of taste, aroma, and appearance. This research provides important insights into the possibilities of using natural ingredients to create visually appealing and healthy drinks. This research shows that making mocktails with kencur rice and ginger is well received by customers and has the opportunity to develop in the hospitality industry. In addition, the use of these natural ingredients supports sustainability efforts and can help preserve culinary traditions and improve the welfare of local farmers.